Analysis of Science Generic Skills in Animal Respiration Practicum: Is it Improved Through Guided Inquiry-based Learning? - Trya Adi Nur Destryani; Ria Yulia Gloria; Dede Cahyati Sahrir (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
Practicum not only advanced skills to use the practicum tools, but also basic skills, known as science generic skills, which emphasize students’ ability to understand, identify, and solve presented problems. This study aims to analyze students’ activities in animal respiration practicum, investigate their generic science skills after conducting the animal respiration practicum, and describe their responses to guided inquiry-based animal respiration practicum. This study employed the pretest-posttest control group designs. The data were collected using tests, observations, and questionnaires. Afterward, the collected data were analyzed using descriptive qualitative analysis. The results showed that the students’ generic skills in guided inquiry-based animal respiration practicum are categorized as high shown in their learning activities. The students who apply the inquiry model and students who apply the conventional model have significantly different improvements in generic science skills. Moreover, the students very positively respond to the guided inquiry-based animal respiration practicum. This study concludes that the practicum has allowed students to understand the actual learning process.